The Effect of Early Nutrition Intervention on Rebleeding Patient with Eshophageal Varices After Ligation ; Literatur Review - Sonang Veronika Butarbutar; Agung Waluyo; Riri Maria (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Esophageal varices bleeding can be treated with ligation. Patients with active bleeding varices generally tend to have a fairly high incidence of rebleeding. Many studies explain that early feeding can increase the risk of recurrent bleeding. Objective: The objective of this study to identify the effect of nutrition intervention on rebleeding after ligation in patient with esophageal varices. Method: The method of this systematic review used PICO formulation (Population, Intervention, Comparation, and Outcome). This review used online database including, ProQuest, PubMed, ScienceDirect, Willey online, and Google Scholar with the search strategy used PRISMA. Article selected by inclusion criteria: Journal international, Full text, using experimental research and within at least 10 years publication, adult research respondent. We included 4 studies related to early nutrition intervention on rebleeding Patient with Eshophageal Varices After Ligation who have been tested for quality with CASP and JBI. Result: The result if this study only 4 article met criteria inclusion. The result of this systematic review on 4 articles explain that feeding nutrition is safe not cause bleading in patient and early eating had no impact on how frequently ligation patients experienced recurrent bleeding. Providing nutrition using the ligase approach has been shown to be both feasible and safe.